Study on the optimization of the enzymatic hydrolysis of antimicrobial protein from Moringa oleifera Leaves by response surface method - Huang, Zhilian; Kang, Dandan; Li, Jihua; Guo, Changqing; Peng, Shaodan (IOP conference series. Earth and environmental science, 2020)
Moringa oleifera leaves contains antimicrobial protein, which is absent of optimized extraction and systematic analysis. The aim of this work is to provide a systematic research of its protein isolate hydrolysate on the optimized extraction via the response surface method and the functional properties. The isolated protein was obtained by alkali extraction and acid precipitation, which purity was 81.12%±0.03%. Through the response surface method, the result of the optimization obtained the enzymatic hydrolysis of antimicrobial protein was as follows, the substrate concentration of 5.09%, the Bromelain enzyme dosage of 3883.42 U/g, pH 7.0 and temperature of 55 °C for 3.64 h . And the protein hydrolysate was indicated that the purity was 88.59%±0.13%. Moreover, the ash, the crude fat and moisture were declined significantly compared with the protein isolate. This subject could provide basic theoretical basis for the application of M. oleifera leaves protein.